Small RNAs containing the pathogenic determinant of a chloroplast‐replicating viroid guide the degradation of a host mRNA as predicted by RNA silencing - Navarro, Beatriz; Gisel, Andreas; Rodio, Maria Elena; Delgado, Sonia; Flores, Ricardo; Di Serio, Francesco (The Plant journal : for cell and molecular biology, 2012)
Summary How viroids, tiny non‐protein‐coding RNAs (∼250–400 nt), incite disease is unclear. One hypothesis is that viroid‐derived small RNAs (vd‐sRNAs; 21–24 nt) resulting from the host defensive response, via RNA silencing, may target for cleavage cell mRNAs and trigger a signal cascade, eventually leading to symptoms. Peach latent mosaic viroid (PLMVd), a chloroplast‐replicating viroid, is particularly appropriate to tackle this question because it induces an albinism (peach calico, PC) strictly associated with variants containing a specific 12–14‐nt hairpin insertion. By dissecting albino and green leaf sectors of Prunus persica (peach) seedlings inoculated with PLMVd natural and artificial variants, and cloning their progeny, we have established that the hairpin insertion sequence is involved in PC. Furthermore, using deep sequencing, semi‐quantitative RT‐PCR and RNA ligase‐mediated rapid amplification of cDNA ends (RACE), we have determined that two PLMVd‐sRNAs containing the PC‐associated insertion (PC‐sRNA8a and PC‐sRNA8b) target for cleavage the mRNA encoding the chloroplastic heat‐shock protein 90 (cHSP90), thus implicating RNA silencing in the modulation of host gene expression by a viroid. Chloroplast malformations previously reported in PC‐expressing tissues are consistent with the downregulation of cHSP90, which participates in chloroplast biogenesis and plastid‐to‐nucleus signal transduction in Arabidopsis. Besides PC‐sRNA8a and PC‐sRNA8b, both deriving from the less‐abundant PLMVd (−) strand, we have identified other PLMVd‐sRNAs potentially targeting peach mRNAs. These results also suggest that sRNAs derived from other PLMVd regions may downregulate additional peach genes, ultimately resulting in other symptoms or in a more favorable host environment for viroid infection.